ANALISIS HUKUM ISLAM TENTANG PENETAPAN HAK WASIAT WAJIBAH TERHADAP AHLI WARIS NON MUSLIM (STUDI PUTUSAN NO. 0141/PDT.P/2012/PA. SBY) - MUHAMMAD HEKKI MIKHAIL (PREMISE LAW JURNAL, 2015)
Inheritance law is a law which regulates the transfer of right in inheritance (tirkah) to an heir, determines who will have the right to be the heir, and determines the shares of each heir. The research was descriptive analytic with judicial normative method. Wasiat wajibah (a will which has to be fulfilled) is a will which is intended for an heir or the relatives who do not obtain the shares of the dead man’s inheritance because of the religious prohibition. In the Islamic point of view, a non-Moslem heir does not get inheritance from a Moslem family, and a non-Moslem is prohibited to bequeath an inheritance from a Moslem, based on the provision in the Koran and Hadits. The reason for giving a wasiat wajibah to a non-Moslem is that people analogize the giving of the right for wasiat wajibah to an adopted child/adoptive father as humanitarian basis and love because of heredity relationship. The Supreme Court’s view on the Ruling No. 0140/Pdt.p/2012/PA. Sby is that an apostate child cannot get inheritance from his Moslem parents, but he can get wasiat wajibah because of justice only. Keywords: Islamic Inheritance Law, Wasiat Wajibah, Non-Moslem heir